Perancangan Perabot Praktis untuk Indekos Di Surabaya - Domas Abdiel Gita Efrata; Grace Mulyono (Intra, 2020)
Many people especially students who graduate from universities or young people who go to Surabaya to look for work will choose to live in a boarding house. Many boarding houses, especially those with cheap rental rates, do not provide facilities such as tables or shelves. It would be more convenient for the resident that if they are provided with some furnitures for them to do their activities or even just to put their belongings which makes it the main purpose for the designer to create such ideas for the needs of comfort and living even is it just a boarding house. In this occasion, the designer will build a furniture facility that is a table, chairs and shelves that can be assembled so that the user can easily carry it and of course the furniture facilities really help the user to carry out certain activities comfortably. Furniture facilities are made by observing, making prototypes according to the design schematic and evaluating the prototype to be a product that fits the user's needs.